Archivi orali per la ricerca linguistica: l'italiano torinese - Daniela Mereu (RiCognizioni)
Oral Archives for Linguistic Research: Turin Italian. This paper aims to present the research project Archivi orali per la ricerca linguistica: l'italiano torinese (‘Oral Archives for Linguistic Research: Turin Italian’), designed to document and describe the variety of Turin Italian through a collection of oral sources dating back to the second half of the 20th century, i.e. the Fondo Giorgina Levi Arian, preserved also in digitised form at the Archivio della Fondazione Istituto Piemontese “Antonio Gramsci”. Among other documents, the Fund also contains 100 recordings (most of them interviews), collected by Giorgina Levi, a teacher, politician and historiographer from Turin, during the period from 1969 to 1992. In addition to the description of the Fund, this paper will examine the possibility of using this kind of oral sources to explore different strands of research in the field of linguistics and, more specifically, what steps are required to make these data usable in the field of linguistics as well. The observations presented should contribute to the promotion of an extended use of oral history data in linguistics studies.